Combined Thoracoscopic Surgical Stapling and Endobronchial Valve Placement For Lung Volume Reduction With Incomplete Lobar Fissures: An Experimental Pilot Animal Study. Issue 2 (April 2020) - Majid, Adnan; Kheir, Fayez; Alape, Daniel; Chee, Alex; Parikh, Mihir; DeVore, Lauri; Agnew, Alexis; Gangadharan, Sidhu
Abstract : Background: In patients with severe emphysema and complete fissures, bronchoscopic lung volume reduction with valves reduces target lobe volume providing improvement in respiratory symptoms, lung function, quality of life, and exercise capacity. It is estimated that up to 88% of patients with emphysema have at least 1 incomplete interlobar fissure. The aim of this study was to evaluate the feasibility of creating a complete fissure with stapling via minimally invasive video-assisted thoracoscopic surgery (VATS) followed by bronchoscopic valve placement to induce lobar collapse in a swine model. Methods: Chest computed tomography (CT) scans were performed on 2 swine and at least 1 target incomplete fissure was identified. Both swine underwent VATS to complete the target fissure using a surgical stapler, followed by bronchoscopic placement of the Spiration endobronchial valves. A chest CT scan was performed immediately postprocedure. Follow-up bronchoscopy and CT scans were performed 2 weeks after the initial procedure prior to sacrifice. Results: Successful fissure completion was accomplished using VATS and confirmed at postmortem explanted lung gross examination. Flexible bronchoscopy 2 weeks following valve placement showed proper positioning of the valves. Effectiveness of combined procedures was confirmed by a chest CT scan that showed complete atelectasis of the target lobe at 2-week follow-up. There was no perioperative or postoperative morbidity or mortality. Conclusion: Combined minimally invasive VATS fissure stapling with bronchoscopic valve placement to induce lobar atelectasis appears safe and feasible in the swine model. Future research in humans using a combined procedure is needed to confirm safety and clinical efficacy.